2000
DOI: 10.1126/science.288.5467.863
|View full text |Cite
|
Sign up to set email alerts
|

Template Boundary in a Yeast Telomerase Specified by RNA Structure

Abstract: The telomerase ribonucleoprotein has a phylogenetically divergent RNA subunit, which contains a short template for telomeric DNA synthesis. To understand how telomerase RNA participates in mechanistic aspects of telomere synthesis, we studied a conserved secondary structure adjacent to the template. Disruption of this structure caused DNA synthesis to proceed beyond the normal template boundary, resulting in altered telomere sequences, telomere shortening, and cellular growth defects. Compensatory mutations re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
142
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(146 citation statements)
references
References 23 publications
3
142
1
Order By: Relevance
“…We performed computational alignment using CLUSTALX (24) and folding using ALIFOLD (25) of the nucleotide sequences of the single-copy TER RNA (TER) gene, identified by BLAST, in the genomes of the five Saccharomyces species from the sensu stricto group available in the National Center for Biotechnology Information database (S. cerevisiae, S. paradoxus, S. bayanus, S. mikatae, and S. kudriavzevii) and of the full-length TER gene that we cloned and fully sequenced from S. kudriavzevii and S. cariocanus. We compared the resulting predicted structures with those of six Kluyveromyces yeast species described previously (15)(16)(17). Conserved primary nucleotide sequences CS1, CS3, and CS4 had been identified before only in the Kluyveromyces yeasts (Fig.…”
Section: Identification Of a Phylogenetically Conserved Pseudoknot Amongmentioning
confidence: 99%
“…We performed computational alignment using CLUSTALX (24) and folding using ALIFOLD (25) of the nucleotide sequences of the single-copy TER RNA (TER) gene, identified by BLAST, in the genomes of the five Saccharomyces species from the sensu stricto group available in the National Center for Biotechnology Information database (S. cerevisiae, S. paradoxus, S. bayanus, S. mikatae, and S. kudriavzevii) and of the full-length TER gene that we cloned and fully sequenced from S. kudriavzevii and S. cariocanus. We compared the resulting predicted structures with those of six Kluyveromyces yeast species described previously (15)(16)(17). Conserved primary nucleotide sequences CS1, CS3, and CS4 had been identified before only in the Kluyveromyces yeasts (Fig.…”
Section: Identification Of a Phylogenetically Conserved Pseudoknot Amongmentioning
confidence: 99%
“…Alignment, performed in Clustal X (1.64b), was facilitated by deletion of the highly variable and partially dispensable (Roy et al 1998) sequence between the template and the 5Ј element of the template boundary structure (corresponding to S. cerevisiae nucleotides 156-453 and Kluyveromyces lactis nucleotides 82-420). An alignment of the six Kluyveromyces species RNAs among themselves revealed seven regions of high conservation (Tzfati et al 2000;Y. Tzfati and E. Blackburn, in prep.…”
Section: Identification Of a Structural Element Conserved Among Buddimentioning
confidence: 99%
“…Some functions have been ascribed to these sequences. In one case, a longrange base-paired RNA structure has been shown to specify the template boundary (Tzfati et al 2000). Other RNA structures or sequences are involved in the maturation and stability of the telomerase RNP (Mitchell et al 1999;Seto et al 1999;Teixeira et al 2002), and a stem-loop of Saccharomyces cerevisiae telomerase RNA has been shown to have a genetic interaction with the DNA-repair protein Ku ( Fig.…”
mentioning
confidence: 99%
“…The RNA component of telomerase is divided into several unique domains that are critical for normal enzymatic function and assembly of the telomerase enzyme (Betts et al, 1995;Bhattacharyya and Blackburn, 1997;Blackburn, 1996, 1999;Gilley et al, 1995;Pe er et al, 1993;Tzfati et al, 2000). These domains include an alignment domain that facilitates substrate binding to the template domain for polymerization and non-template domains that are probably involved with the binding of the RNA to the telomerase protein components and further involved in modulating enzymatic activity.…”
Section: Telomerase As a Drug Targetmentioning
confidence: 99%